1986
DOI: 10.1104/pp.82.1.336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SO2 and O3 on Production of Antioxidants in Conifers

Abstract: Production of antioxidants was investigated in needles of fir (Abies alba Mill.) and spruce (Picea abies (L.) Karst) after exposure to low concentrations of So2, 03, and a combination of both pollutants. Glutathione reacted most sensitively to pollutants followed by vitamin E and vitamin C. In spruce needles, the overall increase of antioxidants after exposure to air pollutants was lower than in needles of fir. SO2 was more potent than 03. Maximum increase of antioxidants was found in needles after exposure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
54
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 5 publications
9
54
0
Order By: Relevance
“…Glutathione levels and especially the accumulation of GSSG, are believed to be sensitive indicators for oxidative stress Mehlhorn et al, 1986;Smith, 1985). Our results are consistent with the hypothesis that the seedlings experienced increased oxidative processes due to the presence of ozone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Glutathione levels and especially the accumulation of GSSG, are believed to be sensitive indicators for oxidative stress Mehlhorn et al, 1986;Smith, 1985). Our results are consistent with the hypothesis that the seedlings experienced increased oxidative processes due to the presence of ozone.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas our results are consistent with the findings in previous year's needles, the ascorbate content of current year's needles showed a steady increase over the sampling period. Mehlhorn et al (1986) reported increased levels of a-tocopherol in spruce and fir after a 2-year fumigation with ozone or sulphur dioxide in needles sampled in October. Our data for the 7-month period show that a-tocopherol undergoes seasonal changes opposite to those found for glutathione and ascorbate, where the a-tocopherol content increases from spring on, reaches a maximum in summer, and decreases in autumn in both age classes.…”
Section: Discussionmentioning
confidence: 96%
“…If the glutathione and superoxide dismutase do provide an adaptive function by scavenging free radicals, as has been suggested (29), one would expect that the plants at 21 h after ozone fumigation, with their elevated glutathione and superoxide dismutase, would be less susceptible to another ozone exposure. This raises the intriguing possibility that plants can be acclimated to ozone exposure and perhaps much of the contradictory field evidence gathered may be the result of data gathered from acclimated and nonacclimated plants.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been no published reports of the initial effects of ozone on the scavenging system of plants. Antioxidant increases have indeed been shown to occur in plants (21) after prolonged ozone exposure but no information is available on the pattern of antioxidant accumulation. In this report we document the initial effects of ozone on some aspects of the antioxidant scavenging system of plants.…”
mentioning
confidence: 99%
“…For example, Mehlhorn et al (1986) reported that the contents of ascorbate, glutathione, and oL-tocopherol increased in needles of conifers after long-term exposure to 0.037 • 10 -6 m s m -s of Os and 0.004 • 10 -6 to 0.012 • 10 -6 m s m -a of SO2. Tanaka and Sugahara (1980) showed that poplar (Poplus euramericana L.) trees which had been exposed to a relatively low level of SO2 (0.10x 10 .6 m s m-a), were more resistant to subsequent treatment with 2• 10 .6 m s m -s SO2.…”
mentioning
confidence: 99%